Optimization and characteristics of selfnanoemulsifying drug delivery system (snedds) components diclofenac sodium fractional method factorial design (ffd) - setiyawan, ferdinta; Herman, Herman; Imba, Farhan (LPPM Akafarma Sunan Giri Ponorogo, 2025)
S SelfNanoEmulsifying Drug Delivery System (SNEDDS) is a drug delivery system designed to increase the solubility and bioavailability of active substances that are difficult to dissolve in water, such as sodium diclofenac. Diclofenac sodium SNEDDS was optimized using FFD. Variables: oil, surfactant, co-surfactant, and mixing time. Responses: droplet size, PDI, and drug loading. Evaluation: DLS, UV-Vis, and stability tests. This study aims to optimize the formulation of SNEDDS sodium diclofenac using the Fractional Factorial Design (FFD) method to obtain a formula with the best characteristics. The main parameters analyzed include entrapment efficiency (%), vesicle size (nm), zeta potential (mV), and polydispersity index (PDI). The results showed that Formula F12 was the best formula with the highest desirability value (0.96). This formula has an entrapment efficiency of 92.5%, the smallest vesicle size (118 nm), and high electrostatic stability with a zeta potential of -36.0 mV and a low polydispersity index (0.20). In addition, Formulas F8 and F4 are also included in the optimum category with desirability values of 0.94 and 0.92, respectively. With small vesicle size and high stability, this SNEDDS formula has the potential to increase the bioavailability of diclofenac sodium, so it can be further developed as a more effective drug delivery system in pharmaceutical applications.